Pendampingan Pengelolaan Website Nagari Guna Mendukung Keterbukaan Informasi Publik di Kenagarian Batipuah Baruah - Eka Vidya Putra; Reno Fernandes; AB Sarca Putera; Rika Febriani; Emizal Amri; Ayu Adriyani (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The team ensures that the program is participatory and on target by dialogue with the community and Nagari Batipuah Baruah government. From this dialogue found the essential issues related to public information disclosure. Among them, the understanding of the Nagari Batipuah Baruah apparatus regarding Information Commission Regulation No. 1 of 2018 concerning Village Public Information Service Standards that have not been developed; also, the capacity of the Nagari government apparatus that has not been fully trained to enter and update information and data on the Nagari official website. The solution to this problem is to carry out activities facilitated with assistance directly involving the Nagari Batipuah Baruah government and other related parties. This community service program aims to increase the knowledge, understanding, and ability of the Nagari Batipuah Baruah government to implement village public information services and optimize digital platforms so that public information disclosure can be achieved. The method of implementing the activities is socialization, Focus Group Discussion (FGD), and training entirely run offline by complying with health protocols. After all the methods were implemented, the Nagari Batipuah Baruah government apparatus received a positive response from the Musyawarah Kerja Sekretaris Nagari (MKSN), which responded to the issue of public information disclosure by holding a meeting with the Nagari Secretary throughout the Tanah Datar Regency. In addition, the problem with the Nagari Batipuah Baruah website, which previously did not appear on the Google search page, had to be searched manually by typing www.batipuahbaruah.web.id has also been resolved through this service program.